Why are some prices stickier than others? Firm-data evidence on price adjustment lags - Daniel Dias; Carlos Robalo Marques; Fernando Martins; Jo\~ao M. C. Santos Silva (European Central Bank (ECB), 2011)
Infrequent price changes at the firm level are now well documented in the literature. However, a number of issues remain partly unaddressed. This paper contributes to the literature on price stickiness by investigating the lags of price adjustments to different types of shocks. We find that adjustment lags to cost and demand shocks vary with firm characteristics, namely the firm's cost structure, the type of pricing policy, and the type of good. We also document that firms react asymmetrically to demand and cost shocks, as well as to positive and negative shocks, and that the degree and direction of the asymmetry varies across firms.
Keywords: C41; D40; E31; 330; Firm heterogeneity; Panel-ordered probit; real rigidities; survey data